in Crisis : Early Detection of Young Children’s Mental Health During the Covid-19 Pandemic in Indonesia - Rohimi Zamzam; Fatiha Khoirotunnisa Elfahmi; Agida Hafsyah Febriagivary; Irwan Baadilla (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The Covid-19 pandemic has an impact on every aspect of human life, one of which is the mental health of the children. There are drastic changes in the child's life cycle and activities that cause mood fluctuations, feelings of sadness, fear, that cause excessive stress reactions. The Covid-19 pandemic is a difficult situation for children, even the impact affects their future. Therefore, there is a need for early detection to track children's mental health. This research aimed to inform teachers' in Bekasi city of their understanding of children's mental health conditions during the Covid-19 pandemic. The purpose of this research is that teachers will have skills in early detection of mental health in children. The method employed descriptive analysis and used survey methods, and questionnaires in collecting the data. The results of this study reveal that early detection knowledge is very important to be understood by teachers as a preventive step in preventing young children's mental health disorders in the future, so that children can be productive and active again to live their lives